Internet infrastructure : networking, web services, and cloud computing - Fox, Richard, 1964-, (Taylor & Francis, a CRC title, part of the Taylor & Francis imprint, a member of the Taylor & Francis Group, the academic division of T&F Informa, plc, 2017)
"Internet Infrastructure: Networking, Web Services, and Cloud Computing provides a comprehensive introduction to networks and the Internet from several perspectives: the underlying media, the protocols, the hardware, the servers, and their uses. The material in the text is divided into concept chapters that are followed up with case study chapters that examine how to install, configure, and secure a server that offers the given service discussed. The book covers in detail the Bind DNS name server, the Apache web server, and the Squid proxy server. It also provides background on those servers by discussing DNS, DHCP, HTTP, HTTPS, digital certificates and encryption, web caches, and the variety of protocols that support web caching. Introductory networking content, as well as advanced Internet content, is also included in chapters on networks, LANs and WANs, TCP/IP, TCP/IP tools, cloud computing, and an examination of the Amazon Cloud Service. Online resources include supplementary content that is available via the textbook's companion website, as well useful resources for faculty and students alike, including: a complete lab manual; power point notes, for installing, configuring, securing and experimenting with many of the servers discussed in the text; power point notes; animation tutorials to illustrate some of the concepts; two appendices; and complete input/output listings for the example Amazon cloud operations covered in the book."--Provided by publisher.